2013
DOI: 10.1123/ijsnem.23.6.601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeine on Upper-Body Anaerobic Performance in Wrestlers in Simulated Competition-Day Conditions

Abstract: Under simulated competition day conditions mimicking four consecutive wrestling matches, acute caffeine ingestion has a partially detrimental effect on upper body intermittent sprint performance in trained wrestlers. Elevated HR and blood lactate levels observed between tests after caffeine ingestion suggest that caffeine may impair recovery between consecutive maximal efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 34 publications
3
46
0
1
Order By: Relevance
“…Previous studies have reported benefits after caffeine ingestion on high-intensity exercise [ 10 , 11 , 16 , 28 ], as well as during taekwondo combat simulation [ 14 ]. However, not all studies have shown a positive effect of caffeine with no performance changes shown during successive maximal cycling bouts [ 29 ], wrestling [ 30 ], and judo [ 17 ]. Similarly to our results, Lopes-Silva et al [ 17 ] showed that caffeine ingestion did not improve performance (number of throws) during the Special Judo Fitness Test after a 5-day weight loss period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported benefits after caffeine ingestion on high-intensity exercise [ 10 , 11 , 16 , 28 ], as well as during taekwondo combat simulation [ 14 ]. However, not all studies have shown a positive effect of caffeine with no performance changes shown during successive maximal cycling bouts [ 29 ], wrestling [ 30 ], and judo [ 17 ]. Similarly to our results, Lopes-Silva et al [ 17 ] showed that caffeine ingestion did not improve performance (number of throws) during the Special Judo Fitness Test after a 5-day weight loss period.…”
Section: Discussionmentioning
confidence: 99%
“…An upper-body intermittent sprint performance (UBISP) test developed by Hickner et al (1991) has been shown to produce similar high blood lactate concentration as an actual competitive wrestling match (Aedma et al 2013;Aschenbach et al 2000;García-Pallarés et al 2011;Hüb-ner-Wozniak et al 2006;Timpmann et al 2012;Walberg Rankin et al 1996) and the wrestlers tested have confirmed receiving a wrestling-like fatigue feeling post-test (Hickner et al 1991). Furthermore, upper-body anaerobic peak power (PP) and mean power (MP) attained in highintensity arm-cranking exercise are considered important success factors for wrestling (García-Pallarés et al 2011;Hübner-Wozniak et al 2006).…”
mentioning
confidence: 79%
“…The modified protocol has been described in detail by Aedma et al (2013). Briefly, cycle ergometer (Monark ® Ergomedic 894 E, Monark, Sweden) with pedals replaced by handgrips was employed.…”
Section: Upper-body Intermittent Sprint Performance Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Portanto, a ingestão de cafeína pode ajudar a reverter a redução no desempenho no período da manhã.Soussi et al (2013) examinaram se a cafeína poderia influenciar o desempenho de atletas de judô em diferentes períodos do dia. Para tanto, foram avaliados 12 atletas de judô, os quais realizaram dois testes no período da manhã (06:00 -07:00 horas) após a ingestão de cafeína (5 mg.kg -1 da massa corporal) e placebo e dois testes no período da noite (17:00 horas) após a ingestão de cafeína (5 mg.kg -1 da massa corporal) e placebo Aedma et al (2013). investigaram o efeito da ingestão de cafeína sobre o desempenho de lutadores de luta olímpica durante simulação de competição.…”
unclassified